1954
DOI: 10.1103/physrev.96.773
|View full text |Cite
|
Sign up to set email alerts
|

Short-Lived Radio-Nuclides Produced by a Synchrocyclotron

Abstract: A method of studying short-lived radio-nuclides produced by the internal beam in a synchrocyclotron is described. Preliminary results on a number of proton-produced activities in the mass range below 70 are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

1961
1961
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 4 publications
4
44
0
Order By: Relevance
“…Sc 48 is also produced by the transmutation V 51 + n 1 ? Sc 48 + He 4 , its half-life being 41 ± 3 h.'' This half-life agrees with the currently accepted value of 43.67 (9) h. 49 …”
Section: Scsupporting
confidence: 69%
See 1 more Smart Citation
“…Sc 48 is also produced by the transmutation V 51 + n 1 ? Sc 48 + He 4 , its half-life being 41 ± 3 h.'' This half-life agrees with the currently accepted value of 43.67 (9) h. 49 …”
Section: Scsupporting
confidence: 69%
“…9 Be targets were bombarded with 132 MeV/u 76 Ge ions accelerated by the Coupled Cyclotron Facility at the National Superconducting Cyclotron Laboratory at Michigan State University. 58 Sc, 59 Sc, and 60 Sc were produced in projectile fragmentation reactions and identified with a two-stage separator consisting of the A1900 fragment separator and the S800 analysis beam line.…”
Section: -61mentioning
confidence: 99%
“…Recent work on the lithiumboron reactions in this laboratory has shown that the lower levels of the residual nuclei tend to be formed with a cross section proportional to 2J+1, where J is the residual nuclear spin. 6 More recent unpublished work in this laboratory shows this is also true of the lithiumberyllium reactions. Under these circumstances one would expect observable amounts of gamma radiation from any bound residual nucleus level if such a level exists and if gamma radiation is possible.…”
Section: Introductionmentioning
confidence: 81%
“…"[The figure] represents the two-dimensional plot (energy loss versus time-of-flight) obtained under these conditions after 40 h integration time with an average intensity of 150 enA. The new species 35,36 Mg, 38,39 Al, 40,41 Si, 43,44 P, 45,46,47 S, 46,47,48,49 Cl, and 49,50,51 Ar are clearly visible." 37 Mg 37 Mg was discovered by Sakurai et al in 1996 as reported in "Production and identification of new neutron-rich nuclei, 31 Ne and 37 Mg, in the reaction 80A MeV 50 Ti + 181 Ta" [46].…”
Section: 30 Mgmentioning
confidence: 99%
“…Therefore, 23 Al is bound to 22 Mg+p by 146±82 keV and is nucleon stable." Previously a 130 ms activity was assigned to either 23 Al or 22 Mg [38]. 24…”
Section: Almentioning
confidence: 99%